Propagation thresholds of competitive integrodifference systems. Issue 12 (2nd December 2019) - Pan, Shuxia; Lin, Guo; Wang, Jingxuan
ABSTRACT: This paper deals with the propagation thresholds of competitive integrodifference systems, which may be non-monotone even if the interspecific competition vanishes. The purpose is to establish the propagation thresholds that two competitors invade a new habitat. We first obtain the minimal wave speed by presenting the existence and non-existence of non-trivial travelling wave solutions. Then we confirm the minimal wave speed is the spreading speed of one competitor if the initial condition admits non-empty compact support.